COVID-19 Vaccine Hesitancy in the United States: A Systematic Review - Yasmin, Farah; Najeeb, Hala; Moeed, Abdul; Naeem, Unaiza; Asghar, Muhammad Sohaib; Chughtai, Najeeb Ullah; Yousaf, Zohaib; Seboka, Binyam Tariku; Ullah, Irfan; Lin, Chung-Ying; Pakpour, Amir H. (Frontiers in Public Health, 2021)
Vaccine hesitancy in the US throughout the pandemic has revealed inconsistent results. This systematic review has compared COVID-19 vaccine uptake across US and investigated predictors of vaccine hesitancy and acceptance across different groups. A search of PubMed database was conducted till 17th July,2021. Articles that met the inclusion criteria were screened and 65 studies were selected for a qualitative analysis. The overall vaccine acceptance rate ranged from 12% to 91.4%, the willingness of studies using the 10-point scale ranged from 3.58-5.12. Increased unwillingness towards COVID-19 vaccine and Black/African Americans were found to be correlated. Sex, race, age, education level, income status were identified as determining factors of having a low or high COVID-19 vaccine uptake. A change in vaccine acceptance in the US population was observed in two studies, an increase of 10.8% and 7.4% respectively between 2020-2021. Our results confirm that hesitancy exists in the US population, highest in Black/African Americans, pregnant or breastfeeding women and low in the male sex. It is imperative for regulatory bodies to acknowledge these statistics and consequently, exert efforts to mitigate the burden of unvaccinated individuals and revise vaccine delivery plans, according to different vulnerable subgroups, across the country.